Theory for normal state critical Kapitza resistance of ⁴He - Ferrell, R.A.; Bhattacharjee, J.K.; Mukhin, S.I. (Физика низких температур, 1998)
We study a steady state bearing a heat current, Q₀, in the normal state of liquid ⁴He with
constraining geometry, near the lambda point, at temperatures T greater than the lambda temperature, Тλ. Critical order parameter fluctuations near the boundary are incorporated in the expression for the
non-local thermal resistivity. The Kapitza resistance is manifested by the additional temperature rise at
the boundary, as compared with the bulk-extrapolated value. Sensitivity of the calculations to the
application of the Dirichlet boundary condition is discussed.